Japanese firms go for biodegradable electronics.
Are compostable computers on their way? If Fujitsu's novel approach lives up to its promise, you'll soon be flinging your computer away safe in the knowledge that its shell will rot harmlessly in nearby soil. In early June 2002, Fujitsu Ltd. (Tokyo) announced the development of a biodegradable plastic for notebook computers, using new processes that build polymers from corn instead of petroleum. Meanwhile, Sony Corp. (Tokyo) disclosed plans to build a Walkman partially from biodegradable plastics. Such materials could reduce the electronics industry's production of pollutants and greenhouse gases, but they must also be compatible with processes used by recyclers.
Keywords: Fujitsu; Japanese firms; Sony; Walkman; Biodegradable electronics; Biodegradable plastic; Biodegradable plastics; Compostable computers; Corn based polymers; Electronics industry; Greenhouse gases reduction; Notebook computers; Pollutants reduction